A critical approach to Eugenio Raúl Zaffaroni’s theory of shameful criminal law - García Apaza, Jorge Eduardo (2023)
The present research deals with the development of the concept of criminal law proposed by the Argentinean professor Eugenio Raúl Zaffaroni from a critical perspective. It aims to identify the characteristics of this new proposal. As a theoretical framework, we have used the concepts developed by the author and the scientific community in recent publications. The methodology used is documentary observation, through the elaboration of bibliographic files. As a result, we have identified various aporias in the author’s position on abolitionism, the Marxist approach to law and the state, and his proposal of the “fraternal state”, among others. We conclude by asserting that lawfare is, strictly speaking, a non-legal concept. We argue that it is not possible to affirm, as the author proposes, that it is the stage of implementation of the so-called shameful criminal law.